Synthesis, Spectral Characterization and Antimicrobial Evaluation of Schiff Base Cu(II), Ni(II) and Co(II) Novel Macrocyclic Complexes. Issue 4 (2011) - Kumar, Gajendra; Kumar, Amit; Shishodia, Nupur; Garg, Y. P.; Yadav, B. P.
Abstract : A series of Schiff base macrocyclic complexes of the type [HLMX2 ] where M = Cu(II), Ni(II), Co(II) and X = Cl, OAc have been synthesized by condensation of acetylacetone and thiocarbohydrazide (2:2) in the presence of divalent metal salt in methanolic medium. The complexes have been characterized with the help of elemental analysis, conductance measurements, magnetic measurements and their structural configuration have been determined by various spectroscopic (Electronic, IR, 1 H NMR, 13 C NMR, GCMS) techniques. Electronic and magnetic moments of the complexes indicate that the geometries of the metal centers are octahedral. These metal complexes were also tested for their antimicrobial activities to assess their inhibiting potential.